New horizons from big data and artificial intelligence: challenges and opportunities for management, education and social sciences - Dos Santos, Maria José Palma Lampreia (2020)
With increase of digitization, advent of disruptive technologies and their diffusion in the society lead to challenges for today’s business managers, academicians and to global society as a whole. Hence, there is colossal emphasis on data sciences. Today’s consumers including millennials appear far more informed. The socio-economic situations and trends around the globe seem to be rapidly changing. The social and management scientists today are unable to predict the emerging trends, issues, and changing social perspectives cum uncertain environment with 100% accuracy. From governments to private sector, industry, and markets are now more data-driven than ever before. There is an inclination toward big data, data analytics and informed decision-making. This presentation tries to overcome this gap on the literature and presents the latest development, challenges in the themes Big Data and Artificial Intelligence, issues and solutions faced by organizations, communities and societies.